Becoming a phenomenologically skilled researcher – an account of a journey started. Issue 5 (3rd September 2017) - Normann, Anita
Abstract: This methodological article takes the reader on a phenomenological journey through a research process and reflects on three aspects deemed as particularly relevant for the process: (1) considerations leading to a phenomenological approach; (2) aspects related to gathering the material; (3) aspects related to analysing the material. The hermeneutic phenomenological analysis is visualized with examples from a specific study, related to perceptions of practice changes among English as a Second Language (ESL) teachers. By making reflections of an inexperienced researcher transparent, as well as sharing descriptions and experiences of the analysis procedures, this article can be read as a thinking tool for others who walk the same path, but in different shoes.